THE EFFECT OF LEARNING READINESS AND LEARNING MOTIVATION ON LEARNING OUTCOMES IN THE SUBJECT FINANCIAL ADMINISTRATION AT SMKN 62 JAKARTA - Ponco Dewi K; Roni Faslah; Latifah Budiarsih (Jurnal Ilmiah Econosains, 2017)
The method of this research is survey method with causality approach. The population in this research were all the students at SMKN 62 Jakarta. The affordable population were all the 11th grade students of the office administration with total 63 students. Sampling techniques used was proportional random sampling, so the sample in this research is amounted 55 respondents. Data collecting technique, were used logging documents, interviews and questionnaires. To get the data results of the study, done by mid test of financial administration subject in 2nd semester, while learning readiness and learning motivation obtained by giving questionnaires to respondents. Data analysis technique used were the test requirement analysis consists of a normality test and lineariti test, classical assumption test, multiple linear regression test, hypothesis test which consists of t-test and f-test. Based on the results of data analysis can be known that there are partially effect between learning readiness with learning outcomes. It can be seen from the results of data analysis which shows tcount 2,235 > ttable 1,675. Learning motivation partially effects on learning outcomes, it’s seen from the results of the data analysis that shows tcount 4,090> ttable 1,675. Learning readiness and learning motivation simultaneously effect on learning outcomes, it’s seen by data analysis that shows fcount 32,299 > ftable 3,175. The obtained regretion equation is . Based on determination of the coefficient test R2 is 0,554 that’s means learning readiness and learning motivation effects on learning outcomes amount 55,4%. Keywords: Learning Readiness, Learning Motivation, Learning Outcomes